A qualitative analysis of work conflict in state government institution : a case study of Hulu Terengganu district and land office - Wan Mohamed Hilmi Wan Isa
Conflicts are detrimental to the organization and regarded as a negative part of organizational behavior that needs to manage and resolve. Furthermore, based on the Malaysian Psychological Wellbeing Index, the psychological wellness for public servants in Malaysia is at a moderate level, which might indicate the presence of work conflict within the government organization. Motivated by this issue, this research is design to explore the work conflict among the employee of Hulu Terengganu District and Land Office. In achieving the research objective, this study employs the qualitative case-study method, where the author interviewed eleven respondent from eleven Hulu Terengganu Districts and Land Office's divisions. The data from the interviews were analyzed using qualitative data analysis software, ATLAS.ti (ver.7). The study has two important outcomes. Firstly, the author found evidence of work conflict in the Hulu Terengganu District and Land Office. Explicitly, it was found that three types of work conflict exist within the organization, namely Relationship Conflict, Task Conflict, and Process Conflict. Secondly, this study found the elements of conflict management in the Hulu Terengganu District and Land Office. Nine elements of conflict management were found, namely, investigate the cause of conflict, avoid the conflict, ignore the conflict, compromise, negotiate, calm down, report to superior, and listen to others. As for the conclusion this study supports the previous work in this research area by providing new evidence with a new research setting. Besides, these current findings are crucial for the stakeholder to improve work satisfaction and wellbeing among the employee of Hulu Terengganu District and Land Office.